Controllable Eu valence for photoluminescence tuning in apatite-typed phosphors by the cation cosubstitution effect. Issue 46 (18th May 2016) - Li, Guogang; Lin, Chun Che; Wei, Yi; Quan, Zewei; Tian, Ying; Zhao, Yun; Chan, Ting-Shan; Lin, Jun
Abstract : A schematic presentation for the valence transition from 3+ to 2+ of Eu in Ca2(1+ x ) La8(1− x ) (SiO4 )6− x (PO4 ) x O2 :Eu (0 ≤ x ≤ 6) based on the XANES spectroscopy analysis. Abstract : By cosubstituting [Ca 2+ –P 5+ ] for [La 3+ –Si 4+ ] in the Eu-doped Ca(2→8) La(8→2) (SiO4 )6− x (PO4 ) x O2 (0 ≤ x ≤ 6) system, Eu 3+ ions are controllably and gradually transformed to Eu 2+ . Thus, the emission colors consecutively changed from red to blue/green light. Furthermore, excellent warm-white lights with the low correlated color temperature (CCT) range of 3500–3800 K and a high color rendering index ( R a ) (88.4–93.2) have been achieved by mixing the as-prepared phosphors at different cation cosubstitution ratios.